2022
DOI: 10.1186/s12884-022-04900-y
|View full text |Cite
|
Sign up to set email alerts
|

The Maternal Postpartum Quality of Life Instrument (MPQOL-I): development and psychometric evaluation in an exploratory sequential mixed-method study

Abstract: Background “ Postpartum quality of life” refers to women’s satisfaction of their position in life, based on cultural status, expectations, values, attitudes, goals, and living standards. Hence the need to pay attention to more specific dimensions of quality of life in the postpartum period is being sensed. This study was conducted to develop the Maternal Postpartum Quality of Life Instrument (MPQOL-I) and assess its psychometric properties. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A study conducted by Mokhtaryan-Gilani et al demonstrated that breastfeeding women obtained higher scores in questionnaires assessing the quality of life [43]. The frequency of breastfeeding is an important modifying factor.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Mokhtaryan-Gilani et al demonstrated that breastfeeding women obtained higher scores in questionnaires assessing the quality of life [43]. The frequency of breastfeeding is an important modifying factor.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in addition to measuring the impact of diseases, the QDIS-7 can also measure the impact of symptoms (headache and low-back pain in the present study), treatments (21,22), exposures (23,24), and any other specifiable (25) status or condition that might affect regular daily physical, psychological, or social functioning. Applications of the QDIS-7 may include QOL associated with environmental pollution, healthcare workers' QOL, maternal postpartum QOL, and caregivers' QOL, (23,24,(26)(27)(28)(29)(30)(31)(32)(33)(34). None of those examples is a disease, but the QDIS-7 can be used to quantify the specific impact of each one on QOL, using the same metric as for asthma, diabetes, etc.…”
Section: Advantages Over Generic Instrumentsmentioning
confidence: 99%
“…It is indisputable that there are large numbers of tools available for the postpartum period, aimed at identifying signs and symptoms of a physical and psychological nature. There are instruments – self-administered or requiring administration by a professional – to identify aspects such as depression and/or anxiety [ 12 16 ], evaluate urinary incontinence [ 17 ], efficacy with breastfeeding [ 18 20 ], quality of life [ 21 24 ], fatigue [ 25 ], quality of sleep [ 26 ], quality of sexual relations [ 27 ], social support [ 28 ], and the mother–child bond [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%